A study of the transport of lithium across the erythrocyte membrane in vivo and of the effects of the ion transport inhibitors digoxin and dipyridamole. - Wood, A; Aronson, J; Bunch, C; Grahame-Smith, D (1989)
1. We have given an oral load of lithium carbonate to healthy volunteers in order to investigate the transport of lithium across the erythrocyte membrane in vivo and the effects of known inhibitors of that transport. 2. Using this technique we have shown that pretreatment with either digoxin, an inhibitor of the sodium/potassium pump, or dipyridamole, an inhibitor of the anion transporter, does not alter the plasma or erythrocyte lithium concentration profiles, nor any of the pharmacokinetic variables derived from these data, and we conclude that these two transport pathways do not contribute significantly to the in vivo handling of lithium by erythrocytes. 3. We have also shown that erythrocyte lithium concentrations measured directly differ significantly from the predicted concentrations calculated using the two-compartment pharmacokinetic model which has been used in some earlier comparisons of in vitro and in vivo lithium handling. 4. We suggest that the in vivo administration of lithium carbonate may permit a specific measure of the in vivo activity of the sodium/sodium countertransport pathway.